2017
DOI: 10.14196/mjiri.31.96
|View full text |Cite
|
Sign up to set email alerts
|

Leadership challenges in health care organizations: The case of Iranian hospitals

Abstract: Background: Effective leadership is a vital component of health care systems and has an extensive range of functions in improving organizational effectiveness and efficiency. This study aimed at exploring leadership challenges encountered by leaders in Iranian hospitals. Methods: This qualitative study was conducted on a purposeful sample of 27 members of hospital management team in Tehran using face-to-face semi-structured interviews and in-depth interviews. Thematic analysis was used to analyze and report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Further, the need to delegate authority to relevant local institutions and centers to expedite the decisionmaking process was another nding of this study. Unfortunately, the existence of slow bureaucratic structures in Iran has always been considered as one of the obstacles in the face of crises [45]. Notably, Norway was one of the most successful countries in controlling the COVID-19 using the capacity of regional and local enterprises such as municipalities [46].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the need to delegate authority to relevant local institutions and centers to expedite the decisionmaking process was another nding of this study. Unfortunately, the existence of slow bureaucratic structures in Iran has always been considered as one of the obstacles in the face of crises [45]. Notably, Norway was one of the most successful countries in controlling the COVID-19 using the capacity of regional and local enterprises such as municipalities [46].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the need to delegate authority to relevant local institutions and centers to expedite the decisionmaking process was another nding of this study. Unfortunately, the existence of slow bureaucratic structures in Iran has always been considered as one of the obstacles in the face of crises [47]. Notably,…”
Section: Discussionmentioning
confidence: 99%
“…According to Wongprasit (2012), it was found that the leadership competency of the private hospital director in Thailand includes human resource management and development and employee engagement. The study of Ghiasipour et al (2017) found that the challenges of leadership in healthcare organisations were human resources (the number and distribution of human resources, staff empowerment and education, motivational mechanisms, and staff diversity).…”
Section: Discussionmentioning
confidence: 99%